New data from the first discovered paleoparadoxiid (Desmostylia) specimen shed light into the morphological variation of the genus Neoparadoxia - Kumiko Matsui; Ana M. Valenzuela-Toro; Nicholas D. Pyenson (Scientific Reports, 2022)
Abstract Desmostylia is an extinct clade of marine mammals with two major sub-clades, Desmostylidae and Paleoparadoxiidae, known from Oligocene to Miocene strata of the North Pacific coastline. Within Paleoparadoxiidae, three genera have been identified: Archaeoparadoxia, Paleoparadoxia, and Neoparadoxia. The latter taxon is the geochronologically youngest palaeoparadoxiid and Neoparadoxia is characterized by a comparatively larger body size, although it is known only from a few specimens within a short temporal and geographic range. Here we report the discovery of an isolated tooth, which we identify as Neoparadoxia cf. N. cecilialina, constituting only the second individual specimen of Neoparadoxia with preserved dentition yet reported. This specimen was collected near Corona, California, USA, and we attribute it to the “Topanga” Formation, extending the geographic range of this taxon in Southern California. While the exact geographic locality was not recorded when it was collected in 1913, we establish two potential localities based on associated hand-written museum label and new stratigraphic information. Although initially identified as Desmostylus hesperus, this specimen of Neoparadoxia was collected 10 years before the first named paleoparadoxiid from Japan. We expect that description of more complete desmostylian material from elsewhere in Southern California will clarify the taxonomic richness and paleoecological role of this clade in Cenozoic marine mammal assemblages.